Successful Treatment of Fanconi Anemia and T-Cell Acute Lymphoblastic Leukemia - Terrie Flatt; Kathleen Neville; Karen Lewing; Jignesh Dalal (Case Reports in Hematology)
Fanconi anemia is associated with an increased risk of malignancy. Patients are sensitive to the toxic effects of chemotherapy. We report the case of a patient with Fanconi anemia who developed T-cell acute lymphoblastic leukemia. He experienced chemotherapy-related complications including prolonged neutropenia, grade IV vincristine neuropathy, and disseminated aspergillosis. He was successfully treated with modified dosing of cytarabine and intrathecal methotrexate followed by allogeneic bone marrow transplant. The aspergillosis was treated with systemic antifungal treatment and surgical resection. Now 30 months after bone marrow transplant the patient is without evidence of aspergillosis or leukemia.